Development of a loop-mediated isothermal amplification for rapid detection of orf virus - Tsai, Su-Ming; Chan, Kun-Wei; Hsu, Wei-Li; Chang, Tien-Jye; Wong, Min-Liang; Wang, Chi-Young (Journal of virological methods, 2009)
A loop-mediated isothermal amplification (LAMP) assay using six primers targeting a highly conserved region of the B2L gene has been developed to diagnose orf virus. The assay produces a ladder-like pattern of products on an agarose gel that can be specifically digested with BsrGI enzyme. The sensitivity of the LAMP assay, which was determined to be a single copy of the standard plasmid, was 100 fold and 10 fold higher than PCR and nested PCR, respectively; furthermore, no cross-reactivity was founded with the other tested viruses. By staining the products directly in the tube with PicoGreen or ethidium bromide, the products can be visualized with a similar sensitivity as by gel electrophoresis. Clinical samples were tested using PCR, nested PCR and LAMP assay and the positive rates were 60%, 70% and 70%, respectively. The LAMP assay allows easy, rapid, accurate and sensitive detection of infection with orf virus and is especially applicable in a resource-limited situation.